(3JbQjQGJs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es
(3ChdgG (B:s
(3ChdgG(B: (3HMK GdSGJQ GdeZUhH hGddHGS HYO Cf GYJeO Cf dG Odjd aj GdebGe EdG eSFdI GNJQGY GdCeQ hGdfgj Ke Ef GdbjGe NUhUG GdGHJOGFj aj GdUdGI Ohfs
(3BNQgG (B:s
(3BNQgG(B: (3hGeG HGH GddbWI aGdPj jXgQ aj YHGQI GdeJf aj GdLhGgQ Cfg dG jLH GdOaY ddbWI HdG HjfI hGdPj jXgQ ef YHGQI GdLhGgQ Cfg dG jLhR GdOaY HdG HjfI hYOe hLhH GdOaY dG jfGajs
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis